Students’ and Teacher’s Challenges in Distance Learning Implementation in EFL Context in SMK Nusa Dua Toya Anyar Kubu, Karangasem - Ni Kadek Sutami; Made Hery Santosa; Gede Mahendrayana (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
This study aims to investigate the students’ and teacher’s challenges in learning EFL in distance learning context for 162 eleventh grade students and one English teacher in SMK Nusa Dua Toya Anyar Kubu, Karangasem in the academic year of 2020/2021. This study used mixed-method as the data were collected through questionnaire for the quantitative data and interview for qualitative data. The quantitative data were analyzed by using SPSS to find the mean score and used TCR guidelines of categorization developed from Sugiyono (2017), while the qualitative data were analyzed according to the steps by Miles and Huberman (1994). The result of students’ challenges are found that the challenges related to instructional variables (lack of explanation from teachers and limited opportunity to practice four English basic skills) were categorized the highest challenges experienced by the students compared to in institutional and individual variables. In addition, the result for the teacher’s data analysis found that the evaluation and assessment variables are the highest challenges compared to access and motivation variables. Understanding the role of teacher as the instructor in distance learning is important to improve students’ ability and can minimize the students’ challenges in distance learning. Keywords: Distance learning, EFL, Learning Challenges